RELASI KUASA DALAM PUISI “ENGKAU YANG MENULIS PUISI, AKU YANG MENANDATANGANI” KARYA NIZAR QABBANI DALAM PERSPEKTIF PIERRE BOURDIEU (PENELITIAN KRITIK SASTRA POST-STRUKTULARISME) - Maolidan, Iqbal; Romadhoni, Moh. Syahrul Zaky; Nugraha, Rahmat Mulya (Jazirah: Jurnal Peradaban dan Kebudayaan, 2022)
One of the famous poets (poetry creators) of his time was Nizar Tawfiq Qabbani (1923-1998) from Damascus. Most of his poetry deals with the themes of romance, politics, and feminism. Unfortunately, literary works are often "extinct" due to lack of support from readers. To preserve a literary work, something is needed to take care of it. Literary criticism is a tool to preserve literary works. And there are many theories of literary criticism that can be used as a tool to use in research. The aim of this research is to find out the poet way builds power relations according to Pierre Bourdieu between men and women in the poem. This research is a type of qualitative research, and researcher apply the documentation method in collecting data in this study. Researcher used descriptive and analytical approaches to analyze the data in this study. And the results of this research is that the power relations between men and women in the selected poem contradict what happened in real life. In general, men will always be in power, and men will always have the power to control or dominate. So that men become the main figures in the upper class or in Pierre Bourdieu's theory it is said to be the dominant class, while women are lower. However, it is inversely proportional to this poem by Nizar Qabbani. The researcher found in this poem that women are strong creatures, women can do anything by themselves. Even in this verse, women are demanded not to always be submissive and obedient just because the culture and society that have been passed down from generation to generation look down on them.